Creative reality counseling model: Acceptability and effectiveness at improving self-regulated learning - Purwadi Purwadi; Wahyu Nanda Eka Saputra (International Journal of Evaluation and Research in Education (IJERE), 2023)
Counselors use the reality counselling model to help counselees overcome their problems, including the problem of self-regulated learning. As professionals, it is necessary for them to identify the elements that can improve the success rate of this model. One of the elements is creative art, and its use in integration with the aforementioned model will form what is termed creative reality counseling model. The aim of this article was to identify the acceptability and effectiveness of the creative reality counseling model to improve self-regulated learning. Borg and Gall’s research and development design was a preferred design for this research, with the involvement of a total of five stages, namely: i) Problem identification;ii) Planning; iii) Product hypothesis drafting; iv) Expert and practitioner judgments; and v) Effectiveness testing. The acceptability of the product was analyzed using the interrater reliability Cohen’s kappa, while the effectiveness was identified using the Wilcoxon signed-rank test. The research results showed that the creative reality counseling model was acceptable and effective at improving students’ self-regulated learning. These results may offer alternative counseling good practices for counselors to develop students’ self-regulated learning.